2014
DOI: 10.1111/ina.12134
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an energy efficiency retrofit on indoor air quality

Abstract: To investigate the impacts of an energy efficiency retrofit, indoor air quality and resident health were evaluated at a low-income senior housing apartment complex in Phoenix, Arizona, before and after a green energy building renovation. Indoor and outdoor air quality sampling was carried out simultaneously with a questionnaire to characterize personal habits and general health of residents. Measured indoor formaldehyde levels before the building retrofit routinely exceeded reference exposure limits, but in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 27 publications
0
44
1
1
Order By: Relevance
“…Formaldehyde concentrations were found to be significantly higher (p=0.004) in homes immediately post renovation as compared to pre-renovation (0.03 vs. 0.01 ppm). The significant increase in the levels of formaldehyde, however, was not consistent with the findings of previous studies which either reported significant decrease of the formaldehyde level (Frey et al, 2015) or failed to find its increase in the green buildings post-renovation. In the current study, an increase in indoor formaldehyde levels post-renovation can be explained by indoor smoking (WHO 2010) amongst other parameters such as the presence of new building material consisting of particleboard and plywood, which could potentially contain formaldehyde-based resins (WHO 2010).…”
Section: Resultscontrasting
confidence: 97%
“…Formaldehyde concentrations were found to be significantly higher (p=0.004) in homes immediately post renovation as compared to pre-renovation (0.03 vs. 0.01 ppm). The significant increase in the levels of formaldehyde, however, was not consistent with the findings of previous studies which either reported significant decrease of the formaldehyde level (Frey et al, 2015) or failed to find its increase in the green buildings post-renovation. In the current study, an increase in indoor formaldehyde levels post-renovation can be explained by indoor smoking (WHO 2010) amongst other parameters such as the presence of new building material consisting of particleboard and plywood, which could potentially contain formaldehyde-based resins (WHO 2010).…”
Section: Resultscontrasting
confidence: 97%
“…The possibility of acrylic-based paints to not be only VOCs free [56] but also able to remove indoor VOCs by adsorption has been tested.…”
Section: Depolluting Capacitymentioning
confidence: 99%
“…In addition, reductions in an apartment's extreme indoor temperature conditions correspond with improvements in its resident's reported health measures of general quality life/health, emotional distress, and sleep – key health issues for older adults. In another component of the larger study, reductions in formaldehyde levels marginally corresponded with reduced emotional distress and had no correspondence with quality life/health or sleep over the 1‐year time period (Frey et al., ). But formaldehyde reductions in the short term (i.e., 3‐month post‐renovation) did correspond with improvements in quality of health/life and reductions in emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Further information about the renovation process is described in Frey et al. () and Ahrentzen et al ().…”
Section: Methodsmentioning
confidence: 99%